Ekstraksi Polifenol Total dari Herba Suruhan (Pepperomia pellucida (L)Kunth.) menggunakan Malic Acid-Glucose Based Microwave Assisted Extraction - Muhammad Safruddin; Nur Mita; Islamudin Ahmad (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
This study aims to determine the effect of the use of malic acid-glucose based microwave assited extraction (MAE) methods on total polyphenol extraction from suruhan herbs (Pepperomia pellucida (L) Kunth.). Samples that have been dried in the extraction using solvents (green solvent) Malic Acid-Glucose with a ratio of 1: 2, 1:3 and 1: 4 g/g in several conditions including, microwave strength 30% for 5 minutes with a sample ratio and a solvent of 1:14 g/mL. Then the extract solution obtained was measured in total polyphenol levels using the folin ciocalteu (FC) reagent and the absorbance was measured at a wavelength of 658 nm using a UV-vis spectrophotometer. Based on the results of the study obtained levels of polyphenols from each condition of the solvent used is 85 mg GAE/g sample (1 : 2 g/g solvent), 696 mg GAE/ g sample (1:3 g / g solvent) and 317 mg GAE /g sample (1: 4 g / g solvent). From this study it can be concluded that the method of malic acid-glucose based microwave assited extraction can be used to extract polyphenol compounds from Suruhan herbs quickly, easily and efficiently.